Efektivitas Model Pembelajaran Think Pair Share dalam Meningkatkan Pemahaman Siswa Terhadap Materi Ide Pokok dan Ide Pendukung Teks Deskripsi di Kelas IX-I SMP Negeri 13 Surabaya - Aurora Putri Nidya; Sueb Hadi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Through classroom action research conducted in two cycles, this study aims to improve the understanding of grade IX-I students of SMP Negeri 13 Surabaya on the material of main ideas and supporting ideas of descriptive texts by implementing the TPS cooperative learning model. The results of the study showed a significant increase in student understanding after the implementation of the Think Pair Share learning model. In the pre-cycle, the average student test score was 65. After cycle I, the average score increased to 78, indicating an increase of 20%. In cycle II, the average score reached 85, or an increase of 9% from cycle I. This increase is indicated by the increasing number of students who can correctly identify the main idea and supporting ideas of descriptive texts. In addition, student activeness in discussing and giving opinions also increased significantly. This shows that the Think Pair Share cooperative learning model is effective in improving students' understanding of the main idea and supporting ideas of descriptive texts.